Willingness to Communicate in Arabic Among Secondary Islamic Boarding School Students in Cambodia: A Mixed-Methods Study - Rahmawati Rahmawati; Zaimatuz Zakiyah; Fitrah Dinanti Massofia; Ade Sri Wahyuni; Nabil Gustian (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
Learners' Willingness to Communicate (WTC) is widely recognized as a key indicator of success in language learning, as higher levels of WTC are associated with more effective and meaningful language use. This study investigates students' WTC in Arabic at An Nikmah Al-Islamiyah Islamic Boarding School in Phnom Penh, Cambodia, along with the factors that support and hinder its development. This area remains underexplored in non-Arab contexts involving Muslim minority populations. Employing a convergent parallel mixed-methods design, this study used a survey as the primary method, complemented by qualitative data from observations, interviews, and documentation, with thirty students participating. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through triangulation. The findings indicate that students' WTC in Classroom contexts was moderate (M = 2.45), whereas their WTC outside the Classroom was low (M = 2.00). Students were more willing to communicate in memorization-based tasks or when prompted by teachers, but showed limited engagement in spontaneous communicative situations. Supporting factors included high learning motivation, a supportive learning environment, and varied instructional methods. In contrast, inhibiting factors included limited facilities, mismatched teacher backgrounds, differences in students' proficiency levels, and minimal opportunities for Arabic practice outside the Classroom. The study concludes that enhancing WTC requires holistic, environment-based pedagogical interventions in Arabic language learning within non-Arab Muslim minority contexts, while also extending WTC research beyond its traditional focus on English language learning.